PENINGKATAN AKTIVITAS BELAJAR SISWA DAN KEMAMPUAN KOMUNIKASI MATEMATIKA UNTUK KIMIA DENGAN MODEL PEMBELAJARAN LEARNING CYCLE 5E DI KELAS XI-IPA 2 MAN MODEL SINGKAWANG TAHUN PELAJARAN 2013/2014 - Sutardi Sutardi; Irwandi Irwandi; Taslima Taslima; Rahmi Nuraztia (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2016)
Learning has been done using the learning cycle 5E model for material buffer and salt hydrolised solution in class XI-IPA MAN Model Singkawang academic year 2013/2014. The main purpose of this research is to increasing students learning activity and improvement of mathematic communication for chemistry that previously could not be done with the lecture method. Learning cycle 5E model has five steps: engagement, exploration, explanation, elaboration/extention, and evaluation. The first step, engagement, teacher give some oral questions to stimulate students’s interest in learning proccess. The second step, exploration, students learn together in small groups to study and discuss the material given. The third step, explanation, students explain the concept with their own words and compare their opinion with the other. Next step, elaboration, in this step students applied the concept and skill they have learned to answer the questions. Last, evaluation, teacher evaluate the teaching learning process by giving assessment/post test. Learning cycle 5E model has been proven incresing students learning activity and improvement of mathematic communication for chemistry showed that there is significant improvement in the result of observation learning activity and communication mathematic test. This learning model also proven to help students to understand the subject matter, particularly for buffer and salt hydrolised solution, as demonstrated by the results of post-test and test formative (daily tests) where the majority of students get good value (above KKM set).